A Pragmatic Analysis of Young Children’s Speech Acts During Shared Book Reading Interactions - Indira Fitri Apriani; Syihabuddin Syihabuddin; Mahardhika Zifana (UIN Salatiga, 2026)
This study examines young children’s speech acts during shared book reading within a natural family setting. The data consist of 151 naturally occurring utterances produced by two children aged 5 and 7 years (RA and NH) while reading several storybooks with their mother. Using a descriptive qualitative approach, the study employed recording, transcription, utterance unit identification, and coding based on Searle’s classification of speech acts and Austin’s concept of illocutionary functions. The findings reveal that representative acts dominate the children’s utterances (81), followed by directives (31), expressives (30), and commissives (9). Declarative acts were absent, as young children do not yet possess the social authority required to perform linguistically transformative actions. The analysis also shows distinct pragmatic patterns between the two children: NH produced more representative and inferential utterances, whereas RA tended to use expressive and directive acts when responding to the story and illustrations. These results demonstrate that shared book reading provides a rich context for eliciting diverse speech acts and highlights developmental differences in the pragmatic abilities of children aged 5–7. This study contributes to the field by presenting naturalistic data from an Indonesian family context and by emphasizing the role of shared book reading interactions in shaping early pragmatic development.